If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 5 + 1 Combine like terms: 5 + 1 = 6 6x = 6 Solving 6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 1 Simplifying x = 1
| q+9+2q+5q= | | 5r-10r+8rs= | | 19y-10= | | 5t+7t-1= | | 12rt-10r+18t= | | 18+k=8 | | (10b-9)-3(3b+3)=-3 | | E^1/2x=1/2 | | y-0.06y=29546773 | | (10b-9)-3(3b+3)=3 | | s+14=p | | y-0.02y=5660807 | | 1/625=5^3x-1 | | 5W-12=3W | | y-0.3y=744590 | | [x]=900 | | 14m-5=109 | | 9x^2+5x=46 | | x+(-21)=8 | | (7+3)/3 | | 7+3/3 | | X^2=-31 | | 6y+9-4y+-4=7y-10 | | j+1=0 | | (x/16)=4 | | 6(n+3)=7n-8 | | i+1=0 | | X-2/2=5 | | y-0.09y=255406 | | 5x+10-3=4x+5 | | 5ny^3-7x-3ny^3+8x=0 | | 12x-4y=-8 |